2022
DOI: 10.1007/s00228-022-03378-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation

Abstract: This study aimed to investigate the interactions between posaconazole (POS) and intravenously/orally administered Cyclosporine A (CsA) in allogeneic hematopoietic stem cell transplant (HSCT) recipients. MethodsWe included 118 allogeneic HSCT patients who received CsA and POS simultaneously between January 2017 and June 2020 this study. The ratio of CsA blood concentration (ng/mL) to dosage (mg/day) (C/D) before and after POS initiation was compared. ResultsAfter the initiation of POS, the level of CsA increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…POSA increased the mean C/D ratio of CsA to a similar extent in patients with aplastic anaemia in current study (7.60%-184.00%). Studies from Xue et al [27] and Zhu et al [28] indicated that the CsA C/D ratio was found to be approximately 1.5-fold higher after POS initiation in patients underwent HSCT. Here, we showed that the CsA C/D ratio increased 1.97 times when co-administered with POSA in aplastic anaemia patients.…”
Section: Discussionmentioning
confidence: 97%
“…POSA increased the mean C/D ratio of CsA to a similar extent in patients with aplastic anaemia in current study (7.60%-184.00%). Studies from Xue et al [27] and Zhu et al [28] indicated that the CsA C/D ratio was found to be approximately 1.5-fold higher after POS initiation in patients underwent HSCT. Here, we showed that the CsA C/D ratio increased 1.97 times when co-administered with POSA in aplastic anaemia patients.…”
Section: Discussionmentioning
confidence: 97%